People, ideas and stories of soils research: a brief overview - Гавриш, Наталія Степанівна; Гавриш, Н.С.; Гавриш, Наталия Степановна; Havrysh, Natalia S.; Позняк, Степан Павлович; Позняк, С. П.; Pozniak, Stepan P. (Walter de Gruyter, 2021)
The article highlights the exceptional importance of soils in the modern world and the importance of scientific research in soil science, which can be an important means of solving social problems. It is shown that soil resources, as the basis of agricultural development, are the long-term capital through which different nations exist and develop. The current state of soils can serve not only as a characteristic of the development of society, but also as a criterion for assessing the activities of government and social stability of the country.

У статті висвітлюється виняткове значення ґрунтів у сучасному світі та важливість наукових досліджень у ґрунтознавстві, які можуть бути важливим засобом вирішення соціальних проблем. Показано, що ґрунтові ресурси, як основа розвитку сільського господарства, є довгостроковим капіталом, завдяки якому існують і розвиваються різні народи. Сучасний стан ґрунтів може слугувати не лише характеристикою розвитку суспільства, а й критерієм оцінки діяльності органів влади та соціальної стабільності країни.
Pozniak S. People, ideas and stories of soils research: a brief overview / S. Pozniak, N. Havrysh // Soil Science Annual. - Vol. 72(2), 135995. - Walter de Gruyter, 2021. – 4 p.
Keywords: soil; soil resources; social soil science; soil informativeness; soil protection; soil fertility; ґрунт; ґрунтові ресурси; суспільне ґрунтознавство; інформативність ґрунтів; захист ґрунтів; родючість ґрунту; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Soil science